2022
DOI: 10.17245/jdapm.2022.22.5.387
|View full text |Cite
|
Sign up to set email alerts
|

Buffered articaine infiltration for primary maxillary molar extractions: a randomized controlled study

Abstract: Background Dental pain management is an important aspect of patient management in pediatric dentistry. Articaine is considered the most successful anesthetic agent for infiltration anesthesia. Buffered articaine has been observed to have faster onset and longer duration of action with less pain on injection. The aim of this study was to evaluate and compare pain on injection, onset of action, and pain during extraction using buffered (using Sodium bicarbonate (NaHCO 3 ))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…15 In a meta-analysis by Tong et al 16 , a significant reduction of postoperative pain was reported following an articaine injection. In a study by Dhake et al 17 buffered articaine showed significantly lower pain scores, a faster onset, and less pain during the procedure for both subjective and objective evaluation. 17…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…15 In a meta-analysis by Tong et al 16 , a significant reduction of postoperative pain was reported following an articaine injection. In a study by Dhake et al 17 buffered articaine showed significantly lower pain scores, a faster onset, and less pain during the procedure for both subjective and objective evaluation. 17…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Dhake et al 17 buffered articaine showed significantly lower pain scores, a faster onset, and less pain during the procedure for both subjective and objective evaluation. 17…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Further improvement of the diffusion properties of articaine solutions may lead to useful applications in infiltration anesthesia of mandibular molars as an alternative to IANB. Previous studies on the effect of buffering on the clinical efficacy of articaine have demonstrated controversial results [ 6 10 11 ].…”
Section: Introductionmentioning
confidence: 99%